Crystal structure of 1-(4–chlorophenyl)-4-benzoyl-3-methyl-1H-pyrazol-5-ol, C17H13ClN2O2 - Xu Li-Ying; Chen Chen-chen; Chen Meng-Qi; Chang Yue; Sang Rui-ge; Zhang Heng-Qiang (Zeitschrift für Kristallographie - New Crystal Structures)
C17H13ClN2O2, monoclinic, P21/c (no. 14), a = 5.3601(4) Å, b = 10.6233(7) Å, c = 25.2125(16) Å, β = 92.920(5)°, V = 1433.96(17) Å3, Z = 4, Rgt(F) = 0.0495, wRref (F2) = 0.1143, T = 173(10) K.